2021
DOI: 10.1016/j.ymben.2021.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of parameters for genome-scale metabolic models of cultured mammalian cells

Abstract: Genome-scale metabolic models describe cellular metabolism with mechanistic detail.Given their high complexity, such models need to be parameterized correctly to yield accurate predictions and avoid overfitting. Effective parameterization has been wellstudied for microbial models, but it remains unclear for higher eukaryotes, including mammalian cells. To address this, we enumerated model parameters that describe key features of cultured mammalian cells -including cellular composition, bioprocess performance m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 101 publications
0
10
0
Order By: Relevance
“…Composite objective functions can be created, for instance for maximizing biomass. This approach has proved effective in prokaryotes and synthetic biology settings 41 , 42 but less so in mammalian systems 43 and using biomass as the objective function showed a difference between WT and mutant lines but did not clearly discriminate between mutant lines in a way that predicted observed data (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Composite objective functions can be created, for instance for maximizing biomass. This approach has proved effective in prokaryotes and synthetic biology settings 41 , 42 but less so in mammalian systems 43 and using biomass as the objective function showed a difference between WT and mutant lines but did not clearly discriminate between mutant lines in a way that predicted observed data (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Although their model was not specifically tailored to the cell line clone (neither cell-specific model nor cell-specific biomass composition), it was a promising example of how GSMMs facilitated process optimization and avoided time-consuming DoEs. Even though artificial biomass reactions are commonly used for growth simulation as an objective function, [46] this concept might be questionable: Schinn et al [81] showed much more accurate growth predictions when using reactive oxygen species (reactive oxygen species (ROS)) synthesis or mitochondrial reduced nicotinamide-adenine dinucleotide (reduced nicotinamide-adenine dinucleotide (NADH)) regeneration as objective function for example. This aspect needs to be studied in more detail since selecting an appropriate objective function is one of the most fundamental pillars of the simulation of GSMMs.…”
Section: Cho Models As Opportunity To Reconstruct Mammalian Cell Modelsmentioning
confidence: 99%
“…While some attempts have been made to measure CHO cell GEM predictive performance (Schinn et al, 2021b ; Széliová, 2021a , 2021b ), the effectiveness of CHO cell GEMs at capturing both intracellular flux distributions and extracellular phenotypes has not been comprehensively assessed. In this paper we present an evaluation of extracellular and intracellular predictive capabilities of CHO cell GEMs, using a holistic 13 C‐labeled fluxomic assessment methodology.…”
Section: Introductionmentioning
confidence: 99%